2003
DOI: 10.1002/gps.1005
|View full text |Cite
|
Sign up to set email alerts
|

Family carers' responses to behavioural and psychological symptoms of dementia

Abstract: Few carers articulated clear strategies to deal with behavioural and psychological symptoms. For most, tolerance proved more effective and less distressing than arguments and reprimands. Carers' responses are likely to be influenced by social and cultural factors and may differ in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Four studies were identified that involved interviews with carers about their BSPD management strategies (Dodds, 1994;Harvath, 1994;Ward et al, 2003;Colling, 2004). Ward et al (2003) undertook interviews with 50 Australian family carers regarding BPSD experienced by their relatives and the strategies used by them. They found that the most common response to symptoms was to not respond at all.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies were identified that involved interviews with carers about their BSPD management strategies (Dodds, 1994;Harvath, 1994;Ward et al, 2003;Colling, 2004). Ward et al (2003) undertook interviews with 50 Australian family carers regarding BPSD experienced by their relatives and the strategies used by them. They found that the most common response to symptoms was to not respond at all.…”
Section: Introductionmentioning
confidence: 99%
“…Heeren O et al 2003 Wandering was higher in males. Ward S et al 2003 CGs reported wandering in 8% of mild, 14% of moderate, and 12% of severe dementia cases. 34% of carers whose family members wandered considered it a problem.…”
Section: Discussionmentioning
confidence: 97%
“…It is commonly accepted among experts that CG of persons with dementia have a major influence on the tone and quality of the relationship and interpersonal responses within the dyad, with emphasis on accommodating techniques such as: good communication, attentiveness, creativity, affection, reassurance, persistence, patience, flexibility, consideration, compassion, tolerance, emotionally responsive interactions, understanding, attribution of behaviors to the disease rather than a personal affront, and awareness that one's own responses can escalate or alleviate behaviors (Cohen-Mansfield, 2001;Farran, Loukissa, Perraud, & Paun, 2003;Smith, 2004;Ward, Opie, & O'Connor, 2003). Communion, or a shared sense of reality and affective state, is suggested as an appropriate person-centered approach during interactions, with emphasis on staying within the person with dementia's frame of reference, listening and asking only open-ended questions, without demanding or questioning, and leaving the initiative to the person with dementia (Normann, Henriksen, Norberg, & Asplund, 2005).…”
Section: Behavioral Symptoms As a Dyadic Consequencementioning
confidence: 98%